Design of Modified Single-Layer Double U-Type Linear to Circular Polarization Convertor - Haoming Hu; Dongfang Zhou; Guohu Chen; Tianpeng Li; Jun Gao (International Journal of Antennas and Propagation)
This paper proposes single-layer periodic arrays of freestanding slot frequency-selective surface (FSS) as an approach to convert linearly polarized wave to circularly polarized wave. The double U-type structure is etched on a metal plate rather than a traditional print circuit board (PCB) material. It has the characteristics of broadband and could be applied to the situation of large incident angles. Numerical simulations have been carried out, and the prototype structures have been fabricated and experimentally validated. The whole thickness is only 1 mm, and the results show that 3 dB axial ratio (AR) bandwidth is 36.6% at normal incident (16.5% at ±60°). An insertion loss of under 3 dB can be achieved within the whole AR bandwidth.